Ca2+ sensor-mediated ROS homeostasis: defense without yield penalty. (September 2022) - Kandhol, Nidhi; Singh, Vijay Pratap; Wang, Yizhou; Chen, Zhong-Hua; Tripathi, Durgesh Kumar
Abstract : Constitutively active immunity against pathogen infection affects the growth and yield of plants. Gao and colleagues recently demonstrated that a Ca 2+ sensor, RESISTANCE OF RICE TO DISEASES1 (ROD1), regulates an immune suppression network that consolidates reactive oxygen species (ROS) metabolism and Ca 2+ -sensing to equilibrate both defense responses and optimal growth in plants.